Analysis Of The Moral Message In The Film Srimulat: Hil Yang Mustahal - Lesmana, Sandi Putra; Hariyanto, Didik (Universitas Muhammadiyah Sidoarjo, 2024)
The primary objective of this research is to investigate the implicit moral messages conveyed in the film